Coaches on Fire or Firing the Coach? Evidence of the Impact of Coach Changes on Team Performance from Italian Serie A - Alessandro Argentieri; Luciano Canova; Matteo Manera (Fondazione Eni Enrico Mattei (FEEM), 2019)
In this paper, football data from the 2007/2008 to 2016/2017 seasons of the Italian Serie A were used to identify the effects of replacing a coach mid-season due to poor team performance. We used an instrumental variable approach to correlate coach turnover within a season with player productivity and found a very low positive impact of the coach change in the short term but a significant negative impact in the long term. Our findings are also relevant to the literature on management replacement in small-size firms.
Keywords: C23; C36; M51; Z22; 330; Italian Football Data; Coach Changes; Team Performance; Models for Panel Data; Instrumental Variables